A comparison of measured versus self-reported anthropometrics for assessing obesity in adults: a literature review. Issue 5 (July 2018) - Maukonen, Mirkka; Männistö, Satu; Tolonen, Hanna
Aims: Up-to-date information on the accuracy between different anthropometric data collection methods is vital for the reliability of anthropometric data. A previous review on this matter was conducted a decade ago. Our aim was to conduct a literature review on the accuracy of self-reported height, weight, and body mass index (BMI) against measured values for assessing obesity in adults. To obtain an overview of the present situation, we included studies published after the previous review. Differences according to sex, BMI groups, and continents were also assessed. Methods: Studies published between January 2006 and April 2017 were identified from a literature search on PubMed. Results: Our search retrieved 62 publications on adult populations that showed a tendency for self-reported height to be overestimated and weight to be underestimated when compared with measured values. The findings were similar for both sexes. BMI derived from self-reported height and weight was underestimated; there was a clear tendency for underestimation of overweight (from 1.8%-points to 9.8%-points) and obesity (from 0.7%-points to 13.4%-points) prevalence by self-report. The bias was greater in overweight and obese participants than those of normal weight. Studies conducted in North America showed a greater bias, whereas the bias in Asian studies seemed to be lower than those from other continents. Conclusions: With globally rising obesity rates, accurate estimation of obesity is essential for effective public health policies to support obesity prevention. As self-report bias tends to be higher among overweight and obese individuals, measured anthropometrics provide a more reliable tool for assessing the prevalence of obesity.